Qualitative Study: Analysis of Interpersonal Relationships of Female Students Using the Niqab - Annida Dahrul; Cintya Sukma Widita; Muflihah Awaliyah Sufti; Sekar Dwi Wulandari; Eva Agustian (Utan Kayu Publishing, 2022)
The purpose of this interpersonal relationship analysis is to make the community have an overview of the interpersonal relationships of female students who choose to wear the veil. It can be seen from the motives, factors and environmental responses to the choice of the subject who chooses to wear the veil. This study uses a qualitative approach to interpretive phenomenology. The technique used in this research uses in-depth interviews and observation. The research results show a specific picture of how the subject establishes interpersonal relationships with the environment both from a psychological and social perspective. Based on the research results, it can be seen that each subject has different problems in interpersonal relations, both from within or psychological aspects or problems from the perspective or perspective of the environment and the surrounding community.